Will you accept without knowing what? A Thuringian newspaper experiment of the Yes-No Game - Werner Güth; Oliver Kirchkamp (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Many economic experiments are run in the laboratory with students as participants. In this paper we use a newspaper experiment to learn more about external validity of lab research. Our workhorse is the Yes-No game. Unlike in ultimatum games responders of the Yes-No games do not know the proposal when deciding between whether to accept it or not. We use two different amounts that can be shared (100 and 1000). In line with findings for the ultimatum game, offers were fairer and rejections less likely when participants are older and submit their decisisons via mail rather than the Internet. By comparing our results with other studies (using executives or students), we demonstrate, at least for this type of game, the external validity of lab research.
Keywords: C91; C93; 330; Verhandlungstheorie; Test; Zeitung; Internet